A risk assessment model of acute liver allograft rejection by genetic polymorphism of CD276. Issue 6 (1st May 2019) - Yu, Xiaobo; Wei, Bajin; Su, Rong; Yao, Jia; Feng, Xiaowen; Jiang, Guoping; Xie, Haiyang; Wu, Jian; Xu, Xiao; Zhang, Min; Zheng, Shusen; Zhou, Lin
Abstract: Background: Liver transplantation is an effective therapy for end‐stage liver diseases and acute liver failure. After the operation, however, recipients may suffer grafts loss induced by alloimmune reaction, which is termed as acute allograft rejection. The interaction between costimulatory molecules, CD276, and its ligand, TREML2, promotes T cell‐mediated immune response, as well as acute or chronic allograft rejection. Our research aimed at correlating genetic polymorphisms of CD276 / TREML2 with acute rejection, and evaluating its prognostic value of acute rejection after liver transplantation. Methods: The study enrolled a total of 388 recipients. Among them, acute allograft rejection was observed in 54 cases. We performed single nucleotide polymorphism genotyping of CD276, including rs11072431, rs11574495, rs12593558, rs12594627, rs2127015, rs3816661 and rs7176654, and TREML2, including rs4714431, rs6915083, rs7754593, and rs9394767 from preoperative peripheral blood genome DNA. Results: We found rs2127015 of CD276, rs6915083 and rs7754593 of TREML2, and HBV infection as well were associated with acute rejection. And, rs2127015 influences CD276 expression. Moreover, we established a risk assessment model, composited by statistically proved risk factors. Conclusion: By integrating both clinical and genetic variables, liver transplant recipients can be categorized into different risk groups, and might benefit from individualized therapies. Abstract : Recipients might suffer an allograft acute rejection, soon after the liver transplantation. We found genetic polymorphisms of costimulatory molecule, B7‐H3, and its ligand, TLT‐2, and HBV infection as well were associated with acute rejection. Thus, we deduced a risk assessment model, composited by those statistically proved risk factors, to provide a scoring system to categorize recipients into different risk levels to facilitate individualized therapy.